2021
DOI: 10.1155/2021/6611897
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cannabis on the Clinical and Cytokine Profiles in Patients with Multiple Sclerosis

Abstract: Background. Multiple studies have reported that cannabis administration in multiple sclerosis patients is associated with decreased symptom severity. This study was conducted to evaluate the prevalence of cannabis abuse in multiple sclerosis cases and to evaluate the effect of cannabis on serum cytokines in such cases. Patients and Methods. A total of 150 multiple sclerosis cases along with 150 healthy controls were included during the study period. All cases were subjected to history taking, neurological exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The results of this study were similar to those of other studies, where it was shown that cannabinoids and cannabis extracts efficiently inhibit inflammation by suppressing the levels of pro-inflammatory cytokines. For example, cannabis users who suffered from multiple sclerosis had significantly lower levels of many pro-inflammatory cytokines, such as TNF-α, IL-1, IL-6, IL-12, and IFN-γ, and higher levels of the antiinflammatory cytokine IL-10, in comparison with non-cannabis users [17,44]. Another study reported that cannabis extract high in CBD was superior to pure CBD in reducing the IL-6 and IL-8 levels in an alveolar epithelial cell line, A549, while cannabis extract high in THC used on the same cell line showed only minor anti-inflammatory activity and was more cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were similar to those of other studies, where it was shown that cannabinoids and cannabis extracts efficiently inhibit inflammation by suppressing the levels of pro-inflammatory cytokines. For example, cannabis users who suffered from multiple sclerosis had significantly lower levels of many pro-inflammatory cytokines, such as TNF-α, IL-1, IL-6, IL-12, and IFN-γ, and higher levels of the antiinflammatory cytokine IL-10, in comparison with non-cannabis users [17,44]. Another study reported that cannabis extract high in CBD was superior to pure CBD in reducing the IL-6 and IL-8 levels in an alveolar epithelial cell line, A549, while cannabis extract high in THC used on the same cell line showed only minor anti-inflammatory activity and was more cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were similar to those of other studies, where it was shown that cannabinoids and cannabis extracts efficiently inhibit inflammation by suppressing the levels of pro-inflammatory cytokines. For example, cannabis users who suffered from multiple sclerosis had significantly lower levels of many pro-inflammatory cytokines, such as TNF-α, IL-1, IL-6, IL-12, and IFN-γ, and higher levels of the anti-inflammatory cytokine IL-10, in comparison with non-cannabis users [ 17 , 44 ]. Another study reported that cannabis extract high in CBD was superior to pure CBD in reducing the IL-6 and IL-8 levels in an alveolar epithelial cell line, A549, while cannabis extract high in THC used on the same cell line showed only minor anti-inflammatory activity and was more cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effects of cannabis extracts, as well as their active ingredients, are well documented [ 16 ]. For instance, cannabis users suffering from multiple sclerosis had lower levels of pro-inflammatory cytokines (TNF-α, IL-1, IL-6, and IFN-γ) and higher levels of anti-inflammatory cytokines (IL-10) as compared with non-cannabis users [ 17 ]. Cannabis extracts high in CBD and THC suppressed the expression of IL-6, IL-1β, MCP-1, and TNF-α genes induced by TNF-α/IFN-γ in human 3D EpiDermFT tissue [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a recent prospective case control study showed that the levels of pro-inflammatory cytokines such as IL-1, IL-2, IL-6, IL-17, IL-22, TNF-α, and IFN-γ were significantly increased in the MS group when compared to the MS/cannabis and control groups. Moreover, the same study showed that in the MS population, anti-inflammatory cytokines such as IL-4, IL-10, and interferon-β1 (IFN-β1) had significantly lower values [ 278 ].…”
Section: The Interplay Between Cannabinoid System and Age-related Dis...mentioning
confidence: 99%